AGAMA KEADILAN SEBAGAI NARASI PEMIKIRAN HUKUM ISLAM MASDAR F. MAS'UDI - Mahsun (Al-Mabsut: Jurnal Studi Islam dan Sosial, 2021)
Abstract This article explains Masdar F. Mas'udi's thoughts on the "Religion of Justice" which is the main focus of the theme of Islamic legal thought. The concentration of his studies refers to the two books he has written, namely the religion of justice: the treatise on zakat (tax) Islam and women's reproductive rights: the fiqh dialogue on empowerment. The meeting point of thought in these two books, in addition to the choice of the same paradigm, is also the dominant theme of discussion on benefit, justice, democracy, and human rights (egalitarianism). The discourse and the manifestation of the appropriate methodology were compiled and practiced by Masdar referring to the fields of zakat/taxes and women's fiqh. From the reconstruction of his various thoughts, a lot of controversy emerged. The results of this paper indicate that the paradigms and methods as well as implementation in the practice of ijtihad refer to the areas of zakat, taxes, hajj, and women's issues. In addition, Masdar's thoughts also include spiritual teachings and individual morality and the most important thing is the inspiration of an adequate basic framework of social concepts for an era or modern era that is so complex with human problems in all dimensions. Keywords: religion of justice, qat'i-danni, zakat-tax.